Public Employment Decline in Developing Countries in the 21st Century: The Role of Globalization - Giray Gözgör; Mehmet Huseyin Bilgin; Klaus F. Zimmermann (Global Labor Organization (GLO), 2019)
The impact of globalization on developing countries has been debated: While the "compensation hypothesis" suggests that globalization increases the need for public employees, the "efficiency hypothesis" states that the size of government should be smaller while competing with the world. We are the first to re-visit the debate for 2000-2016 using panel data for 92 developing countries and new innovative bureaucracy and globalization indicators to find robust evidence for the "efficiency hypothesis”.
Keywords: J45; F66; C33; 330; public employment; economic globalization; developing countries; efficiency hypothesis; compensation hypothesis; panel data estimations